"Long-hissler" fine structure within auroral hiss: A review and synthesis. (April 2017) - Kim, Howard F.; LaBelle, James; Spasojević, Maria
Abstract: One of the most prominent fine-structures of auroral hiss is the "long-hissler", defined here as a dispersed feature embedded within broadband auroral hiss emissions in the frequency range 1–40 kHz and lasting longer than 0.3 s. While theory is limited, there is evidence that hisslers can be used in remote sensing of density characteristics at altitudes of thousands of km. By applying an automatic threshold algorithm to VLF data collected at South Pole 2230–0130 UT daily during June–August 2014, 22 h of auroral hiss are identified on 49 of 93 days analyzed, for an occurrence rate of 9.7% during the applicable MLT interval. From manual inspection of these intervals, 414 groups (trains) of long hisslers are identified on 34 of the 49 days on which hiss occurred. Median lower (upper) frequency bounds of these features are 8 (22) kHz, median frequency–time slope is −10 kHz/s, and median hissler repetition time within a train (hissler period) is 1.2 s. Hissler period and frequency–time slope are inversely related. Data from previous studies are reviewed to provide a comprehensive description of the phenomenon. Contrary to some previous studies, subsequent long hissler features are found to commonly overlap in time, and no evidence is found for an inverse relationship between hissler train duration and geomagnetic activity. Abstract : Highlights: Collect data over 93 days, using ground observation of VLF Auroral hiss. Methodology describes how hiss is identified programmatically and dispersive events are identified manually. Characterise frequency, periodicity and slope of dispersive hiss events called hisslers. Compare findings to literature, new data shows larger variety of hissler events than previously seen. Review of current theory for hissler propagation to ground.